Bioprocess parameters and oxygen transfer characteristics in pectin lyase production by Bacillus pumilus - Tepe, Ozlem; Dursun, Arzu Y. (Parlar Scientific Publications, 2017)
The present study aimed at optimization of culture condition for the production of pectin lyase from Bacillus pumilus by submerged fermentation and investigation of the oxygen transfer effects on the enzyme production. Effects of initial pH, carbon and nitrogen sources, aeration, salts and phosphate on microbial growth, pectin lyase activity and released total protein were studied. Optimum pectin and ammonium sulphate concentrations were determined as % 1 (w/v) and 0.05 % (w/v) at pH:8, T:30 °C, 150 rpm, respectively. The maximum microorganism specific growth rate and pectin lyase activity were obtained as 0.0381 (h-1), 14.05 U/mL, respectively. The oxygen transfer coefficient (kLa) and oxygen uptake rate were also determined in a bioreactor. The results showed that, increases in the air feed rate increased the kLa values, B. pumilus produces mainly alkaline pectin lyase and the optimal pH and temperature for the activity were reported as 10 and 40 °C, respectively. © by PSP.
Keywords: Bacillus pumilus. enzymes; Oxygen transfer; Pectin lyase; Volumetric oxygen mass transfer coefficient